Long Non-coding RNA MEG3 Promotes Pyroptosis in Testicular Ischemia-Reperfusion Injury by Targeting MiR-29a to Modulate PTEN Expression - Ning, Jin-zhuo; He, Kai-xiang; Cheng, Fan; Li, Wei; Yu, Wei-min; Li, Hao-yong; Rao, Ting; Ruan, Yuan (Frontiers in Cell and Developmental Biology, 2021)
Increasing evidence shows that the abnormal long non-coding RNAs (lncRNAs) expression is closely related to ischemia-reperfusion injury (I/R) progression. Studies have previously described that lncRNA MEG3 regulates pyroptosis in various organs I/R. Nevertheless, the related mechanisms of MEG3 in testicular I/R has not been clarified. The aim of this research is to unravel underlying mechanisms of the regulation of pyroptosis mediated by MEG3 during testicular I/R. We have established a testicular torsion/detorsion (T/D) model and an oxygen-glucose deprivation/reperfusion (OGD/R)-treated spermatogenic cell model. Testicular ischemic injury was assessed by H&E staining. Western blotting, quantitative real-time PCR, MDA, and SOD tests and immunohistochemistry measured the expression of MEG3 and related proteins and the level of ROS production in testicular tissues. Quantitative real-time PCR and western blotting determined the relative expression of MEG3, miR-29a, and relevant proteins in GC-1. Cell viability and cytotoxicity were measured by CCK-8 and LDH assays. Secretion and expression levels of inflammatory proteins were determined by ELISA, immunofluorescence and western blotting. The interaction among MEG3, miR-29a, and PTEN was validated through a dual luciferase reporter assay and Ago2-RIP. In this research, we identified that MEG3 was upregulated in animal specimens and GC-1. In loss of function or gain of function assays, we verified that MEG3 could promote pyroptosis. Furthermore, we found that MEG3 negatively regulated miR-29a expression at the posttranscriptional level and promoted PTEN expression, and further promoted pyroptosis. Therefore, we explored the interaction among MEG3, miR-29a and PTEN and found that MEG3 directly targeted miR-29a, and miR-29a targeted PTEN. Overexpression of miR-29a effectively eliminated the upregulation of PTEN induced by MEG3, indicating that MEG3 regulates PTEN expression by targeting miR-29a. In summary, our research indicates that MEG3 contributes to pyroptosis by regulating miR-29a and PTEN during testicular I/R, indicating that MEG3 may be a potential therapeutic target in testicular torsion.